2008
DOI: 10.1021/jm700925k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Effects of c(Lys-Lys-Pro-Tyr-Ile-Leu-Lys-Lys-Pro-Tyr-Ile-Leu) (JMV2012), a New Analogue of Neurotensin that Crosses the Blood−Brain Barrier

Abstract: The central administration of neurotensin (NT) or of its C-terminal hexapeptide fragment NT(8-13), produces strong analgesic effects in tests evaluating acute pain. The use of NT-derived peptides as pharmaceutical agents to relief severe pain in patients could be of great interest. Unfortunately, peptides do not readily penetrate the blood-brain barrier. We have observed that the cyclic NT(8-13) analogue, c(Lys-Lys-Pro-Tyr-Ile-Leu-Lys-Lys-Pro-Tyr-Ile-Leu) (JMV2012, compound 1), when peripherally administered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…Subsequently, several additional systemically infused but centrally acting analogs (i.e., NT66L, NT69L, NT79, and ABS212) were synthesized by combining N-terminal modifications and incorporation of non-natural amino acids at positions 8, 9, 11, and 12 (63,64,(68)(69)(70)(71). Finally, in compound JMV2012, the unmodified NT 8-13 fragment has been dimerized and cyclized (72). An advantage of the approach described here is that ANG2002 maintains the full-length sequence of NT, albeit conjugated to a single An2 molecule.…”
Section: Figurementioning
confidence: 99%
“…Subsequently, several additional systemically infused but centrally acting analogs (i.e., NT66L, NT69L, NT79, and ABS212) were synthesized by combining N-terminal modifications and incorporation of non-natural amino acids at positions 8, 9, 11, and 12 (63,64,(68)(69)(70)(71). Finally, in compound JMV2012, the unmodified NT 8-13 fragment has been dimerized and cyclized (72). An advantage of the approach described here is that ANG2002 maintains the full-length sequence of NT, albeit conjugated to a single An2 molecule.…”
Section: Figurementioning
confidence: 99%
“…Contrary to the belief that small molecules with molecular weights under 400 readily cross the BBB, it has been observed that almost 98% of small molecules do not readily cross the BBB. Further, evidence has accumulated that peptides can penetrate the CNS by several different mechanisms [46–49]. These observations clearly indicate molecule size is not the primary factor, but rather the overall physiochemical characteristics of the molecule is critical for BBB transport.…”
Section: The Neurovascular Unit and The Bbbmentioning
confidence: 99%
“…1216 The vast majority of these compounds produce analgesia that is accompanied by hypothermia and hypotension, a feature ascribed to interaction with the NTS1 receptor. 17,18 Reports from the study of the NTS2 selective peptide NT79 ( 1b ) support this notion as it possessed activity against visceral pain but lacked the side effects described above.…”
Section: Introductionmentioning
confidence: 99%